BÎ’AH LUGHAWIYYAH AS A HIDDEN CURRICULUM AND ITS INFLUENCE ON STUDENTS’ SPEAKING SKILLS IN PESANTREN AR-RAUDLATUL HASANAH - Yunus; Bahtiar Siregar; Siti Arfah Daely; Zikriya Husna Aulia Putri; Faisal Hamid (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Arabic language learning in pesantren is not conducted solely through the formal curriculum but also through habituation processes that are internalized in the students’ daily lives. Bī’ah lughawiyyah functions as a language environment that serves as a hidden curriculum at Pesantren Ar-Raudlatul Hasanah, namely an implicit curriculum that shapes language competence in a natural and sustainable manner. This study aims to analyze the role of bī’ah lughawiyyah as a hidden curriculum and its influence on the improvement of students’ speaking ability (mahārat al-kalām). This research employs a qualitative approach with a case study design. The research participants consist of students, Arabic language instructors, and pesantren administrators. Data were collected through participant observation, in-depth interviews, and documentation of language-related activities. The data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing, with data validity strengthened through source and method triangulation. The findings indicate that bī’ah lughawiyyah functions as a hidden curriculum through Arabic language policies, the exemplary practices of instructors, the habituation of communication in daily pesantren life, and non-formal social reinforcement. These practices contribute positively to the enhancement of students’ kalām ability, particularly in terms of speaking confidence, fluency, and spontaneity in oral communication. The findings confirm that bī’ah lughawiyyah as a hidden curriculum plays a strategic role in Arabic language acquisition. Therefore, optimizing the language environment should be positioned as an integral component of Arabic language curriculum development in pesantren.